Research on Spectrum Access Mechanism Based on Polling Scheduling - Jin Lu; Ming Huang; Zhijun Yang (Dianxin kexue)
Dynamic spectrum access is an effective way to improve the spectrum utilization. The spectrum access mechanism based on polling control tends to realize the effective utilization of spectrum resources and rational allocation. A novel polling queuing model, in which the authorized users employ exhaustive service while the cognitive users employ loss service, was proposed. Based on the analysis method of embedded Markov chain and probability generating function, the key parameters of average queue length, bandwidth utilization and forced termination probability were obtained through solving the stationary distribution of equilibrium state. Numerical analysis and simulation results show that the mechanism improves the queuing performance and the bandwidth utilization of spectrum holes, and reveal its potential application in cognitive wireless network for data services.